Features of The Final Judgement Representation in the 16th century Moldavian Painting - Andreea-Irina Stoleriu (Anastasis: Research in Medieval Culture and Art)
The present research has in view an interdisciplinary approach, from a theological and artistic point of view, of the topic of The Final Judgement in some of the most well-known medieval monuments, churches and monasteries from Moldavia. Their walls were magnificently decorated in the 16th century, the scene of The Final Judgement, inspired by different Old and New Testamentar sources, occupies large areas, as a proof of the eschatological topic’s importance since ancient times, represented on the monuments from Arbore, Bălinești, Probota, Humor, Moldovița, Voroneț etc. Moreover, this topic has been of great importance during medieval times, the Renaissance and afterwards, both for the Eastern and Western areas, where various artists made themselves remarked through the usage of different techniques. The focus of the present research paper is represented by the medieval monuments during the reign of Petru Rareș (1527-1538; 1541-1546). This period marked the beginning of a change of vision – including the representation of The Final Judgement, the works of art being decorated with mural painting both indoors and outdoors. Thus conceived, the present study underlines the outlining of some representative aspects in traditional post-Byzantine iconography in Moldavia, the accent falling on the unique way of understanding and approaching this topic by the artists of that period.